STUDY ON ASCORBIC ACID FOR FORTIFICATIONOF RICE CASSAVA - Harun Al-Rasyid; Subeki Subeki; Wisnu Satyajaya; Agus Saptomi (Jurnal Agroindustri, 2017)
Siger rice is an analog rice made from agricultural materials containing carbohydrates such as cassava. The purpose of this research was to know the effect of addition of ascorbic acid and steam duration to the quality of siger rice from cassava. The factorial experiment arranged in a Complete Randomized Block Design (CBRD) with two factors and three replications.. The first factor was the addition of ascorbic acid is 0% (A1), 0.1% (A2), 0.15% (A3), 0.2% (A4), 0.25% (A5), and 0.3% A6). The second factor was steam duration of 25 minutes (L1), 30 minutes (L2), and 35 minutes (L3). The data were analyzed using analysis of variance (ANNOVA) and continued with Least Significance Different (LSD) test. The results showed that the addition of ascorbic acid 0.2% with steaming for 35 minutes resulted in the best quality of siger rice with white color tending, somewhat similar to rice, rather soft, water content of 10.62%, 0.88% ash, protein 3,82%, fat 2.42%, crude fiber 1.13%, carbohydrates 81.12%, and vitamin C 0.61 mg/g.